Glial Activation Markers in CSF and Serum From Patients With Primary Progressive Multiple Sclerosis: Potential of Serum GFAP as Disease Severity Marker? - Abdelhak, Ahmed; Hottenrott, Tilman; Morenas-Rodríguez, Estrella; Suárez-Calvet, Marc; Zettl, Uwe K.; Haass, Christian; Meuth, Sven G.; Rauer, Sebastian; Otto, Markus; Tumani, Hayrettin; Huss, André (Frontiers in Neurology, 2019)
Background: In progressive multiple sclerosis (MS), glial activation is thought to be a relevant mechanism of disability progression. Therefore, in vivo assessment of the glial cell activity is, in the emerging treatment era of primary progressive MS (PPMS), more important than ever. Objectives: To test the association of cerebrospinal fluid (CSF) and serum markers of glial activation in PPMS patients; including glial fibrillary acidic protein (GFAP), chitinase-3-like protein 1 (CHI3L1), soluble variant of triggering receptor expressed on myeloid cells 2 (sTREM2) and marker of neuroaxonal damage (Neurofilament light chain, NfL) as well as clinical severity. Methods: CSF and serum samples from PPMS patients were collected in the MS-centers at Universities of Freiburg (n= 49), Ulm (n= 27), Muenster (n= 11) and Rostock (n= 6). sTREM2 and CHI3L1 levels were measured using the previously reported ELISA assays, while NfL and GFAP were measured using SIMOA assays. Clinical data included age, gender, disease duration, treatment status and Expanded Disability Status Scale (EDSS). Results: 93 CSF samples and 71 matching serum samples were analyzed. The median age of patients was 49 years and disease duration 4.5 years. GFAPserum correlated with EDSS after correction for age (β= 0.3. p= 0.001). Furthermore, EDSS was higher in patients with a GFAPserum level ≥ 151.7 pg/ml compared to patients with GFAPserum below this cut-off (5.5 vs 4.0, p= 0.009). Other markers did not correlate with the clinical severity. Moreover, we found a correlation between NfLCSF and GFAPCSF, sTREM2 and CHI3L1 (ρ = 0.4 for GFAPCSF and sTREM2, ρ = 0.3 for CHI3L1, p < 0.01 for sTREM2 and CHI3L1 and < 0.001 for GFAPCSF). CHI3L1 did not correlate with GFAPCSF but with sTREM2 (ρ = 0.4, p < 0.01). Discussion: The correlation between the glial activation markers in CSF with the markers of neuroaxonal demise supports the notion of the glial involvement in PPMS. The positive correlation between GFAPCSF with disease duration and GFAPserum with the clinical severity of the disease may highlight a particular role of the astrocytes in PPMS and mark the potential of GFAPserum as a disease severity marker.